2000
DOI: 10.1074/jbc.m006766200
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Nucleotide Sequence, and Heterologous Expression of the Biosynthetic Gene Cluster for R1128, a Non-steroidal Estrogen Receptor Antagonist

Abstract: R1128 substances are anthraquinone natural products that were previously reported as non-steroidal estrogen receptor antagonists with in vitro and in vivo potency approaching that of tamoxifen. From a biosynthetic viewpoint, these polyketides possess structurally interesting features such as an unusual primer unit that are absent in the well studied anthracyclic and tetracyclic natural products. The entire R1128 gene cluster was cloned and expressed in Streptomyces lividans, a genetically well developed hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 45 publications
3
97
0
1
Order By: Relevance
“…Examples include enterocin, which is primed by benzoate (13), benastatin, which is primed with hexanoate (14), the R1128 antibiotics, which are primed by a range of short-chain carboxylic acids (15), oxytetracycline, which is primed by malonamate (16), and daunorubicin, which is primed by propionate (17,18). This priming is catalyzed by initiation PKS modules, which vary depending on the priming unit.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include enterocin, which is primed by benzoate (13), benastatin, which is primed with hexanoate (14), the R1128 antibiotics, which are primed by a range of short-chain carboxylic acids (15), oxytetracycline, which is primed by malonamate (16), and daunorubicin, which is primed by propionate (17,18). This priming is catalyzed by initiation PKS modules, which vary depending on the priming unit.…”
Section: Resultsmentioning
confidence: 99%
“…Many other fungal PKSs, however, have a single ACP (15). It was reported in the R1128 anthraquinonelike estrogen receptor antagonist gene cluster that the presence of two acyl carrier proteins is because of the two sets of ketosynthases and acyl transferases with which the ACPs might interact in loading the unusual primer unit (40). The ACPs of R1128 gene cluster are, however, not tandemly repeated and are divergently transcribed unlike mup ACPs.…”
Section: Role Of Tandemly Repeated Acyl Carrier Proteinsmentioning
confidence: 99%
“…While many minimal PKSs use acetate, in the form of acetyl-ACP, to initiate polyketide biosynthesis, a large number of minimal PKSs, such as those from the pathways of enterocin (Piel et al, 2000), R1128 (Marti et al, 2000), doxorubicin (Ye et al, 1994), hedamycin (Bililign et al, 2004;Das & Khosla, 2009) and fredericamycin (Wendt-Pienkowski et al, 2005), have been found to use a variety of non-acetate starter units.…”
Section: Discussionmentioning
confidence: 99%